Non-aneurysmal subarachnoid hemorrhage in a 13-year-old male with infective endocarditis caused by Abiotrophia defectiva: a case report and literature review - Assi, Anas K.; Awwad, Habeeb H.; Sultan, Riman A.; Khaled, Zaina A.; Fatoum, Sara N.; Kharousha, Abdalwahab; Dababseh, Hadi; Adwan, Rabee (Frontiers in Pediatrics, 2025)
IntroductionInfective endocarditis (IE) is a rare but serious condition. It is commonly caused by viridans group streptococci (VGS) or Staphylococcus aureus, often in the presence of structural heart disease. Rare organisms, like Abiotrophia defective (A. defective), can cause IE. Although resistance may not be present in every case, infections caused by this organism are often associated with a more complicated clinical course and may require tailored treatment strategies. In this case, antimicrobial susceptibility testing indicated broad susceptibility, and no resistance was observed in the isolated strain.Case presentationA 13-year-old boy arrived with a severe headache and fever. He had previously been misdiagnosed with infective endocarditis (IE) caused by VGS based on blood cultures and echocardiography, which revealed severe mitral regurgitation (MR), and he received treatment. Despite therapy, he developed a non-aneurysmal subarachnoid hemorrhage (SAH), as confirmed by CT and MRI. A repeat echocardiography revealed mitral valve prolapse (MVP), new vegetations, and pericardial effusion, as a complication of A. defectiva identified later on blood cultures as the causative organism, which led to a revised diagnosis of IE. He remained stable with appropriate treatment, with no neurological abnormalities.ConclusionWe report a case of A. defectiva IE that is exacerbated by non-aneurysmal SAH. It emphasizes the significance of taking IE into account in kids who have neurological symptoms, as well as the necessity of close observation for uncommon but serious causative organisms.